ANALYSIS OF THE APPLICATION OF PUBLIC VALUE IN VILLAGE-OWNED ENTERPRISES (BUMDES) IN THE WARU DISTRICT, SIDOARJO REGENCY - Hariyoko, Yusuf; Wardiyanto, Bintoro; Mufidah, Makhrita (Jurnal Administrasi Negara, 2025)
Currently, villages within the Waru District of Sidoarjo Regency already have Village-Owned Enterprises (BUMDes). There are several running ventures, such as trading in waste incinerators and machineries, educational tourism of metalworking village in Ngingas Village, and rural digital economy in Janti Village. Public value is utilized as valuable inputs for village governments and BUMDes management in carrying out their operational activities. This research aims to analyze and to broadly understand the application of public value in the BUMDes located in Waru District, Sidoarjo Regency. The study applies public value theory as its research focus, emphasizing three essential components that must be fulfilled: legitimacy and support, operational capacity, and substantive value. This research is a descriptive qualitative study. BUMDes in Waru District, Sidoarjo Regency, Indonesia, have successfully generated good public value. The village government’s initiatives have been proven to generate a positive impact on the community. This good public value indicates that BUMDes have been able to provide significant benefits to the local community in terms of the economy, social welfare, and local infrastructure development. Furthermore, indicators of legitimacy and support, as well as operational capacity comprising human resources, technology, and financial aspects, have been achieved. There is also substantive value, encompassing economic, socio-cultural, educational, and ecological values. However, the political value indicator has not yet functioned optimally. Therefore, it is recommended to conduct an evaluation of this indicator and further enhance awarensess campaign regarding BUMDes to ensure broader and more equitable community involvement.